2014
DOI: 10.1590/1517-86922014200401993
|View full text |Cite
|
Sign up to set email alerts
|

Burnout e enfrentamento em jogadores de futebol: fases pré e durante competição

Abstract: rEsumoIntrodução: No contexto esportivo, a falta de estratégias adequadas de enfrentamento e a síndrome de Burnout podem ser fatores limitadores do desenvolvimento e desempenho dos atletas. Objetivo: Avaliar Burnout e formas de enfrentamento entre jogadores de futebol, profissionais e de categorias de base, durante as fases pré-competição e competição. Métodos: Em estudo prospectivo, foram avaliados 73 jogadores de futebol do sexo masculino, sendo 32 profissionais (média de idade = 22 ± 4,14 anos) e 41 amadore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
4
0
3
Order By: Relevance
“…In general, the results showed that during the soccer sports season, seven athletes (13.20%) presented high levels of frequency of feelings of burnout during the 3 periods evaluated (Table 2). When comparing this result with the few findings in the literature that analyzed burnout individually in athletes, it was observed that the results are very similar in relation to the percentage of athletes affected with high levels of burnout 21,27,28 .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In general, the results showed that during the soccer sports season, seven athletes (13.20%) presented high levels of frequency of feelings of burnout during the 3 periods evaluated (Table 2). When comparing this result with the few findings in the literature that analyzed burnout individually in athletes, it was observed that the results are very similar in relation to the percentage of athletes affected with high levels of burnout 21,27,28 .…”
Section: Discussionsupporting
confidence: 60%
“…In Brazil, previous studies on burnout in soccer athletes did not use specific reference tables to assess the levels of frequency of feelings of burnout 18,20,21 . In summary, the search for a specific reference table for a given category and sport modality contributes to a new level of scientific demand, precision, and reliability of burnout behaviors, as well as enabling a more rigorous and precise evaluation, which will result in more effective interventions with athletes by professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dados descritivos para as variáveis de burnout (n=15). 9,00 9,00 9,00 9,00 9,00 9,00 9,00 9,00 9,00 9,00 9,00 9,00 64,00 61,00 66,00 62,00 preocupação em relação à carreira atlética 21 , ou seja, os atletas perceberam o segundo turno da Superliga (M4) como mais importante que o Campeonato Estadual (M2), reforçando a compreensão do burnout como um processo que se desenvolve em resposta ao estresse crônico resultante das intensas rotinas de treinamentos, viagens e competições 22 . Lai e Wiggins 23 também encontraram aumento no índice global de burnout em atletas de futebol universitário ao longo de cinco meses.…”
Section: Discussionunclassified
“…O tipo de pressão que sofre no ambiente de competição, seja por meio da cobrança de treinadores, torcedores e familiares, pode interferir em seu desempenho e potencializar problemas de cunho psicológico e físico. Dessa forma, estratégias de enfrentamento eficazes nessas situações possibilitam mais sucesso e qualidade de vida durante a prática esportiva (Hill & Appleton, 2011;Verardi, Santos, Nagamine, Carvalho, & Miyazaki, 2014).…”
unclassified